2019
DOI: 10.1093/rheumatology/kez090
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of diagnostic delay in axial spondyloarthritis: an analysis based on linked claims and patient-reported survey data

Abstract: Objectives The objective of this study was to assess the current diagnostic delay in axial SpA (axSpA) and to analyse factors associated with it. Methods A stratified sample of subjects with a diagnosis of axSpA (International Classification of Diseases, 10th Revision code M45) was drawn from health insurance data in Germany and was questioned on disease-related, lifestyle and socio-economic characteristics. The diagnostic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
80
4
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 19 publications
12
80
4
11
Order By: Relevance
“…This result was consistent with the data obtained in a prevalence study conducted by Esther [14]. The mean delay of 2.82 ± 1.41 years in disease diagnosis observed in our study was showed similarity with the data reported in various studies [13,15]. 11.86% of the patients (Table 1) had sustained serious infectious diseases before disease symptoms had manifested [p = 0.002; OR 95% CI: 4.434 (1.740-11.300)].…”
Section: Discussionsupporting
confidence: 93%
“…This result was consistent with the data obtained in a prevalence study conducted by Esther [14]. The mean delay of 2.82 ± 1.41 years in disease diagnosis observed in our study was showed similarity with the data reported in various studies [13,15]. 11.86% of the patients (Table 1) had sustained serious infectious diseases before disease symptoms had manifested [p = 0.002; OR 95% CI: 4.434 (1.740-11.300)].…”
Section: Discussionsupporting
confidence: 93%
“…However, there is often a substantial delay between symptom onset and axSpA diagnosis, with recent reports suggesting an average diagnostic delay of 5-14 years [6][7][8][9][10][11]. One factor contributing to the delay in diagnosis of axSpA is the difficulty in distinguishing inflammatory back pain (IBP), a key symptom of axSpA that affects the spine and sacroiliac joints [12,13], from other highly prevalent forms of low back pain in the general population-the overall global prevalence of low back pain is approximately 9% [14], and up to 80% of adults will experience low back pain in their lifetime [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Provision of health services [4] Comorbidity [14] Physical therapy [9] Income and burden of disease [6] Depressive symptoms and burden of disease [19] Diagnostic delay [18] Provision of health services Extra-articular manifestations Comorbidity The claims data were analysed not only for the PROCLAIR respondents (linking claims and survey data), but also for all insured persons who had one of the three diagnostic codes. Therefore, some analyses refer to the total data set of BARMER insurants (e.g.…”
Section: Costs Of Tnf-alpha Inhibitor Therapymentioning
confidence: 99%